Discharge criteria for Crimean–Congo haemorrhagic fever in endemic areas. Issue 4 (April 2016) - Leblebicioglu, Hakan; Sunbul, Mustafa; Bodur, Hurrem; Ozaras, Resat; Barut, Sener; Buyuktuna, Seyit Ali; Guner, Rahmet; Ozkurt, Zulal; Senturk, Gonul Cicek; Yapar, Derya; Yilmaz, Gurdal
Highlights: Risk for household contact transmission is low for Crimean–Congo haemorrhagic fever (CCHF). Thrombocytopenia is a key finding of CCHF. Discharge of cases with CCHF who prone to bleeding must be avoided. There is a need for evidence-based guidelines defining discharge protocols for viral haemorrhagic fevers including CCHF.